Rethinking Journalism Education in Spain: the Gap Between University Studies and the Labour Market - Aldea, Patricia González; Eva Herrero Curiel; Carmen Marta Lazo (European Journal of Social Science Education and Research, 2020)
The main purpose of this paper is to analyse whether professional skills demanded of journalism graduates by companies match university curricula. In the current digital context, adapting journalism studies to labour market changes must be considered. A review of the literature shows much research about this topic in recent years, but, given the rapid changes that occur within a field that is increasingly global and technologically oriented, regular research is necessary. Content analysis has been carried out by evaluating journalism employment offers found on InfoJobs and LinkedIn--the two most used human resources web sites in Spain--and their correspondence to journalism curricula according to ANECA (the Spanish National Agency for Quality Assessment and Accreditation). From an initial sample of 310 job offers, 156 were ultimately selected, discarding those that were repeated or not expressly addressed to journalism graduates. All the information provided in the employment offers was organised into two categories based on the skills required and the descriptive data in the professional profiles demanded. The main findings show not only that it is becoming ever more common for enterprises to look for candidates with abilities which reflect experience closely related to Web 2.0, but also that these same companies apparently tend to ignore traditional journalism skills. It is also true that they do not seem to know precisely what skills a graduate in journalism should have. Knowledge of marketing is included in 47 percent of the positions offered to journalists, when this is not a subject included in journalism curricula.
Keywords: Rethinking Journalism Education in Spain: the Gap Between University Studies and the Labour Market